Bi2Fe4O9 thin films as novel visible-light-active photoanodes for solar water splitting. Issue 16 (5th April 2019) - Wang, Yaqiong; Daboczi, Matyas; Mesa, Camilo A.; Ratnasingham, Sinclair Ryley; Kim, Ji-Seon; Durrant, James R.; Dunn, Steve; Yan, Haixue; Briscoe, Joe
Abstract : Photoelectrocatalytic water oxidation is reported for Bi2 Fe4 O9 for the first time with a faradaic efficiency of 82%. Abstract : We report the chemical solution deposition (CSD) of a phase-pure Bi2 Fe4 O9 thin film for use as a photoanode in photoelectrochemical (PEC) water splitting. The energy levels of Bi2 Fe4 O9 films have been measured and n-type characteristics have been confirmed. With band gaps determined as 2.05 eV (indirect) and 2.80 eV (direct) and valence and conduction bands straddling the water oxidation and reduction potentials, this material is highly promising as a photocatalyst for solar water splitting. The photocurrent of a planar photoanode reached 0.1 mA cm −2 at 1.23 VNHE under AM1.5G illumination. The addition of H2 O2 as a hole scavenger increased the photocurrent to 0.25 mA cm −2, indicating hole injection is one limiting factor to the performance. The performance was enhanced by nearly 5-fold when the Bi2 Fe4 O9 photoanode is coupled to a Co–Pi surface co-catalyst. The photoanode also shows excellent stability with no change in photocurrent over three hours of continuous illumination. These results indicate that this material represents a promising addition to the growing selection of low-cost, stable photocatalysts for use in solar water splitting.